The influence of digital transformation on chinese bank profitability performance - Senbo Zhang (PLoS ONE, 2026)
This paper aims to investigate the impact mechanisms of digital transformation in the banking sector under the rise of financial technology. Utilizing panel data from 116 commercial banks in China from 2011 to 2023, this empirical research employs regression analysis to explore how digital transformation in commercial banks can affect profitability performance. The findings reveal several key points: First, the implementation of digital transformation has not led to improvements in the profitability performance of most commercial banks; rather, it appears to reduce net interest margins and return on assets. Second, digital transformation primarily influences profitability performance through two bridging pathways—operational efficiency and non-performing loan ratio, with both playing a mediating role. Third, digital transformation and inclusive digital finance interact, affecting the profitability performance of banks, where the loan-to-deposit ratio plays a significant role. The heterogeneity of regional inclusive digital finance and banks’ loan-to-deposit ratios also influences the impact of corporate digital transformation on profitability performance. This research not only deepens the theoretical understanding of how digital transformation can help banks enhance their profitability performance but also provides valuable insights and recommendations for managers and operators in the banking sector during the digital transformation process.